Synergic effects of histology subtype, tumor size, and lymph node metastasis on distant metastasis in differentiated thyroid cancer - Liu, Zeming (Ann Transl Med, 2019)
BACKGROUND: Detection of distant metastasis (DM) is important in differentiated thyroid cancer (DTC). This study aimed to investigate the synergic effects of histology subtype, tumor size, and lymph node metastasis (LNM) status on the occurrence of DM in DTC. METHODS: We collected data of 96,788 patients with DTC. Univariate and multivariate analyses were conducted to identify the risk factors of DM. Relative excess risk of synergic effect, attributable proportion of synergic effect, and synergy index were then calculated to assess synergic effects. Further, Kaplan-Meier method using the log-rank test and receiver operating characteristic (ROC) curves were utilized. RESULTS: Age at diagnosis (P<0.001), sex (P<0.001), race (P<0.01), tumor size (P<0.001), N stage (P < 0.001), histology subtype (P<0.001), and extrathyroidal extension (P<0.001) were risk factors for DM in both univariate and multivariate analyses. We also found a significant additive synergic effect between histology subtype and LNM, and between tumor size and LNM on DM in the DTC patients. In addition, patients with follicular thyroid cancer and N1 stage had the sharpest decline in cancer-specific survival curves (P<0.001) and all-cause survival curves (P<0.001) compared to patients with other combinations of histology subtype and N stage. Similar results were obtained in patients with larger tumors (≥10 mm) and N1 stage. The areas under the curve of histology subtype, tumor size, and LNM status were 0.569, 0.744, and 0.681, respectively. CONCLUSIONS: Age at diagnosis, sex, race, tumor size, N stage, histology subtype, and extrathyroidal extension are risk factors for DM in DTC patients. LNM has a synergic effect with either follicular thyroid histology or larger tumor size for higher risk of DM which is important for diagnosing DM.